ARNI effects in HFrEF. Risk reduction beyond LVEF. (3rd October 2022) - Boehmer, A A; Schubert, T; Zezyk, C; Kaess, B; Ehrlich, J R
Abstract: Background: The imbalance of cardiac autonomic nervous system function plays an important role in heart failure associated mortality. ARNI has demonstrated a paramount effect in reducing risk of death and hospitalization for worsening of heart failure. However, its exact mechanism of action remains only partly understood. We sought to prospectively compare heart rate variability as a noninvasive measure of cardiac autonomic nervous system function. Methods: The study design was prospective sequential observational. Patients served as their own internal control. Patients with heart failure with reduced ejection fraction (HFrEF) receiving optimal medical therapy who were scheduled for a switch to ARNI therapy underwent echocardiography and a standardized 30-minute 12-lead Holter ECG recording before starting ARNI therapy. A monitoring of the parameters was performed 3 months after the start of therapy. Physicians were instructed to increase ARNI dose to the highest tolerated or maximum dose. Besides left ventricular ejection fraction (LVEF) we assessed heart rate (HR), standard deviation of normal-to-normal intervals (SDNN) and mean square of differences between consecutive R-R intervals (RMSSD). Results: We recruited 55 patients and baseline characteristics were as follows: age 65±12 years, male sex 78%, NT-proBNP 4989±809 pg/ml, LVEF 28±6%, HR 75±9 bpm, SDNN 43±2 ms, RMSSD 19±2 ms. All patients received beta-blocker therapy and the dosage was similar at baseline and follow-up. After 3 months of ARNI therapy, heart rate showed a significant reduction of 7% (74±14 bpm vs. 69±11 min, P=0.005). SDNN increased by 49% (43±2 ms vs. 64±4 ms, P<0.001) and RMSSD by 42% (19±2 ms vs. 27±3 ms, P=0.01). These results were accompanied by increased LVEF (28±6% vs. 38±10%, P<0.001) and reduced plasma NT-proBNP levels (4989±809 pg/ml vs. 2602±87 pg/ml, P<0.04). NYHA Class of affected patients changed from III to II. Conclusion: After changing from ACE/AT1-I to ARNI, significant improvement of autonomic cardiac nervous system function could be observed. ARNI apparently activates the parasympathetic nervous system as suggested by decreased HR and increased SDNN and RMSSD. Therefore, part of its cardioprotective and beneficial effects may relate to the restoration of autonomic cardiac nervous system function. Potential beneficial effects regarding incidence of sudden cardiac arrest may relate to these observations. Funding Acknowledgement: Type of funding sources: None.